Rabies in the insectivorous bat Tadarida brasiliensis in Southeastern Brazil Raiva no morcego insetívoro Tadarida brasiliensis na região Sudeste do Brasil - Wilson Uieda (Universidade de São Paulo, 1998)
This is the first recorded case of rabies in the insectivorous bat Tadarida brasiliensis in the State of S. Paulo, Southeastern Brazil. The infected bat was found in the afternoon while hanging on the internal wall of an urban building. This observation reinforces the notion as to the caution one must exercise regarding bats found in unusual situations. É registrado o primeiro caso de raiva no morcego insetívoro Tadarida brasiliensis no Estado de São Paulo. O animal raivoso foi encontrado vivo no período da tarde, enquanto pendurado na parede interna de um prédio urbano, o que reforça a noção que se deve ter cuidado com morcegos encontrados em situações não usuais